The Effect of Price, Halal Label, Length of Operating Hours on Users of Online Food Delivery Services in Medan City - Antin Kurnyasih; Sugianto Sugianto; Muhammad Ikhsan Harahap (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study examines the influence of price, halal labels, and operating hours on the decision to use Online Food Delivery services in Medan City. Methods: This study used quantitative research methods with a survey approach and questionnaires as data-collection tools. The study sample consisted of 25 participants. This study used quantitative analysis with a descriptive approach. The study population included all users of online food delivery services on Medan. A total of 100 respondents were selected using purposive sampling. The independent variables in this study were price, halal label, and operating hours, whereas the dependent variable was the decision to use online food delivery services. Data analysis using linear regression. Results: The results indicate that price, halal labels, and operating hours significantly influence the decision to use Online Food Delivery services in Medan City. Price had a significant influence with a t-value of 2.563, halal label with a t-value of 4.757, and operating hours with a t-value of 2.796. Furthermore, collectively, all three variables significantly influenced the decision to use Online Food Delivery services in Medan City, with an F-value of 51.360. Limitations: Decision to use an online food delivery service. Contribution: This research makes a meaningful contribution to the understanding of the effect of Price on Online Food Delivery Service Users in Medan City.